Soft data detection algorithms for an iterative turbo coded MIMO OFDM systems - Kim, K.J.; Reid, T.; Iltis, R.A. (2004 38th Asilomar Conference on Signals, Systems and Computers, 2004)
The use of multiple antennas at both transmitter and receiver can significantly increase the channel capacity. By using orthogonal frequency division multiplexing (OFDM) transmission techniques, a MIMO-OFDM system can achieve high spectral efficiency, which makes it an attractive candidate for high-data-rate wireless applications. In this paper, we propose an iterative soft data detection algorithm, called the soft-QRD-M structure for the MIMO OFDM system, which can incorporate a kind of coding. Iteratively communicating the soft informations between the proposed MIMO data detector and the Turbo decoder, we can improve the BER performance significantly.